Complication Avoidance in Surgical Management of Vertebral Column Tumors - Joshua Feler; Felicia Sun; Ankush Bajaj; Matthew Hagan; Samika Kanekar; Patricia Leigh Zadnik Sullivan; Jared S. Fridley; Ziya L. Gokaslan (Current Oncology, 2022)
The surgical management of spinal tumors has grown increasingly complex as treatment algorithms for both primary bone tumors of the spine and metastatic spinal disease have evolved in response to novel surgical techniques, rising complication rates, and additional data concerning adjunct therapies. In this review, we discuss actionable interventions for improved patient safety in the operative care for spinal tumors. Strategies for complication avoidance in the preoperative, intraoperative, and postoperative settings are discussed for approach-related morbidities, intraoperative hemorrhage, wound healing complications, cerebrospinal fluid (CSF) leak, thromboembolism, and failure of instrumentation and fusion. These strategies center on themes such as pre-operative imaging review and medical optimization, surgical dissection informed by meticulous attention to anatomic boundaries, and fastidious wound closure followed by thorough post-operative care.